Co-utility Theory and Applications - Domingo-Ferrer, Josep; Sánchez, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book explores the theoretical foundations of co-utility as well as its application to a number of areas, including distributed reputation management, anonymous keyword search, collaborative data anonymization, digital oblivion, peer-to-peer (P2P) content distribution, ridesharing for sustainable mobility, environmental economy, business model design and the collaborative economy. It evolved from presentations at the 1st Co-Utility Workshop, "held in Tarragona, Spain, on March 10-11, 2016." How can we guarantee that a global society without a common legal framework operates smoothly? If generosity, honesty and helpfulness do not arise spontaneously, one approach would be to design transactions so that helping others remains the best rational option. This is precisely the goal of co-utility, which can be defined in game-theoretic terms as any interaction between peers in which the best option for a player to maximize her or his utility is to make sure the other players also enjoy a fair share of utility (for example, functionality, security or privacy). Therefore, a protocol or mechanism designed using the co-utility principle ensures that helping others is the best rational option, even if players are selfish.
Co-Utility: Designing Self-Enforcing and Mutually Beneﬁcial Protocols -- On the Different Forms of Individual and Group Strategic Behavior,and Their Impact on Efﬁciency -- Co-Utile P2P Anonymous Keyword Search -- Co-Utile Enforcement of Digital Oblivion -- Self-Enforcing Collaborative Anonymization Via Co-Utility -- Aspects of Coalitions for Environmental Protection under Co-utility.
Keywords: Computational intelligence; Game theory; Computational Intelligence; Game Theory